Penerapan Think Pair Share Berbantuan Padlet dengan Pendekatan Kontekstual untuk Meningkatkan Komunikasi Matematis - Windy Restu Fitriani; Muhammad Fajar Safaatullah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Communication is an essential competency in 21st-century mathematics learning. However, a preliminary study at SMPN 6 Semarang revealed that students’ mathematical communication skills remain low, indicated by the unachieved mathematical expression indicator and suboptimal written text and drawing text. This study aims to assess students’ mathematical communication skills through the implementation of the Think Pair Share (TPS) model assisted by Padlet with a contextual approach, including comparing average learning outcomes with Problem-Based Learning (PBL) and examining improvement. This study employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 64 students from classes VII D and VII E at SMPN 6 Semarang in the 2025/2026 academic year. Data were collected through tests and analyzed using independent and paired t-tests. The results indicate that students taught using TPS assisted by Padlet achieved higher average mathematical communication skills than those taught using PBL, with significant improvement after intervention.